We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
131
1
avatar+83 

(x^2+y^2)^2+2x^2y^2-y^4=x^2(x^2+4y^2)

 

Step-by-step instructions please, thank you!

 Jan 16, 2019
 #1
avatar+102444 
+3

(x^2+y^2)^2+2x^2y^2-y^4=x^2(x^2+4y^2)

 

\((x^2+y^2)^2+2x^2y^2-y^4=x^2(x^2+4y^2)\\ \)

\(LHS\\=x^4+y^4+2x^2y^2+2x^2y^2-y^4\\ =x^4+4x^2y^2\\ =x^2(x^2+4y^2)\\ =RHS\\~\\ QED\)

.
 Jan 17, 2019

6 Online Users

avatar